Konsep Pendidikan Akhlak Menurut Al Ghazali dan Implementasinya di MTs SA Al Islam Jamsaren - Mujiburrohman, Mujiburrohman; Pramono, Agus (TSAQOFAH, 2026)
This study aimed to analyze Al-Ghazali’s concept of moral education (tarbiyat al-akhlaq) and its implementation at MTs SA Al-Islam Jamsaren Surakarta by examining the roles of Islamic Religious Education (PAI) and Guidance and Counseling (BK) teachers, the moral education methods applied, students’ responses and behaviours, the challenges encountered, and the efforts undertaken to address them. The research employed a qualitative approach with a descriptive–analytical design, with data obtained through in-depth interviews with Aqidah Akhlak and Al-Qur’an Hadith teachers and BK teachers, observations of student behaviour, and document analysis. The findings show that moral education at MTs SA Al-Islam Jamsaren Surakarta is implemented in an integrated manner through PAI learning, religious habituation activities, enforcement of school rules, and guidance and counseling services. The methods used include role modelling, habituation, persuasive advice, and the application of educational reward and punishment. Students’ responses to the moral education programs are generally positive, although the level of internalization of moral values varies due to differences in family background, peer environment, and exposure to digital media. The main challenges identified include limited instructional time, diversity of student characteristics, and insufficient synergy with the family environment. Efforts to overcome these constraints are carried out through strengthening teachers’ exemplary conduct, consistently habituating virtuous behaviour, adopting humanistic counseling approaches, and enhancing cooperation between the madrasah and parents. These findings indicate that the implementation of moral education at MTs SA Al-Islam Jamsaren Surakarta is conceptually and practically aligned with Al-Ghazali’s thought, which emphasizes spiritual cultivation, habituation, and gradual, continuous character formation.